Seven ways at once : more classroom strategies and units of work based on the seven intelligences : B.3 - McGrath, Helen; Noble, Toni. (Melbourne : Longman, 1998)
This is a series of three practical teacher references based on Howard Gardner's concept that all of us have seven intelligences, not just one.
Keywords: Education; Cognition; Psychology; Educational psychology; Ability grouping; Learning, Psychology of; Educational psychology; Cognition; Ability grouping in education; Education, Primary